THE ROLE OF RELIGIOUS AND SECULAR VIEWS IN THE SPIRITUAL AND MORAL EDUCATION OF THE YOUNG GENERATION - Madumarovna, Arzimatova Inoyatkhon; Esonalievna, Normatova Dildorakhon; Makhmudovna, Sabirova Zilola; Mukhutdinovich, Akhmadiev Nuriddin (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses religious and secular attitudes, their role and role in the upbringing of young people as one of the important factors in the spiritual and moral education of the younger generation. The author’s remarks are based on the views of great scholars, leading scholars on the importance of religion, religious beliefs, science, worldly knowledge in the spiritual development of the individual, especially the younger generation.